Induced host defense by virulence manipulation of Erysiphe orontii through exogenous application of apoplastic nutrients. (May 2022) - Yousaf, Muhammad Junaid; Hussain, Anwar; Humayun, Muhammad; Iqbal, Amjad; Ali, Fawad; Lee, In-Jung; El-Sabrout, Ahmed M.; Elansary, Hosam O.
Abstract: Host apoplastic nutrients might influence the proliferating biotroph, therefore, we analyzed the effect of host apoplastic nutrients on the virulence strategy of E. orontii (a biotroph model). E. orontii was initially treated with the analogs of commonly found apoplastic nutrients in a culture media. The analogs included Cyanoalanine (CAL), Trehalose, H2 O2, acidic water (0.3% H3 PO4 ), NaNO3, and MgSO4 . After pre-treatment with the analogs of apoplastic nutrients, E. orontii was then inoculated to the host plants. After 5 and 8 days of post-infection (dpi), the virulence of E. orontii was determined through the expression of 20 virulence factor and 7 host defence genes. The expression of AVRk1, Ekal1, Ekal2, Ekal3, Ekal4, Ekal5, Ekal6, Ekal7, Ekal8, Epul5, Epul6, Epul7, Epul8, Epul9, Epul10, Epul11, Epul12, Epul5, Epul17 was determined as a virulence factor and expression of PR1, ERF1, PDF1.2a, PMRs, DMRs, IOS1, MYB3R4 was determined as host defence genes. The results revealed that the tested analogs vigorously affected the phenotypic and genotypic properties of E. orontii and thus its biotrophic virulence strategy. Certainly, the exogenous application of fungal growth-promoting apoplastic nutrients (CAL or TRE) severely reduced the virulence of E. orontii . Contrarily, the stress-inducing apoplastic analogs (H2 O2 or acidic water) surprisingly increased the virulence of E. orontii . Moreover, the application of NaNO3 or MgSO4 decoyed the fungal growth and thus decreasing the E. orontii virulence. Highlights: Analogs of apoplastic nutrients have manipulated E. orontii virulence and the subsequent host defense responses. H2 O2 or acidic water which induced the stress responses increased the virulence of E. orontii. Cyanoalanine or Trehalose which promoted the growth of E. orontii on culture media reduced its virulence to host. NaNO3 and MgSO4 not only increased growth of E. orontii but also enhanced its virulence at initial stages of infection. Abstract : Plant pathogens not only reduce agricultural productivity through yield reduction but also increases the cost of production due to the spray of expensive chemicals which are also dangerous to human health and the ecosystem. A proliferating plant pathogen in a host always relies on the apoplast nutrients found in the host plant's apoplast, xylem, phloem, rhizosphere, and phyllosphere, collectively referred to as nutrient niches, for their growth. We applied a pre-stressed plant pathogen to the host cell to examine its virulence and subsequently the success or failure of a plant's host defense system and identified that the host defended itself from severe virulence by shortening its infection cycle, as evident from high chlorotic areas and a low number of seedlings' death.